‘You have to treat the person, not the mouth only’: UK dentists’ perceptions of communication in patient consultations - Nowak, Marta Justyna; Buchanan, Heather; Asimakopoulou, Koula (Taylor & Francis, 2018)
Effective communication between patients and health professionals is a key component of patient-centred care. Although there is a large body of literature focusing on doctor-patient communication, there has been limited research related to dentist-patient communication, especially presented from the dentists’ perspective. The aim of our study was to explore UK dentists’ perceptions of communication in their consultations, and the factors they perceive may influence this. We conducted semi-structured interviews with eight dentists in UK dental NHS practices. Thematic analysis revealed three themes (‘Treating the whole person’, ‘Barriers to patient-centred communication’ and ‘Mutuality of communication’), which reflected the dentists’ perceptions of their own communication during consultations, the patients’ interaction skills, attitudes (and characteristics that may affect them), and external factors, such as time constraints, that can influence dentist-patients’ encounters. These in-depth accounts are valuable, in that we see what dentists perceive is important, obstructive and facilitative. They report using a patient-centred approach in their everyday dental practice; however this is often difficult due to factors such as time constraints. Although they emphasized that the patient has an active role to play in the communication process, it may be the case that they also need to play their part in facilitating this.